Receptor tyrosine kinase fusions act as a significant alternative driver of the serrated pathway in colorectal cancer development - Chan, Anthony W‐H; Pan, Yi; Tong, Joanna H‐M; Lung, Raymond W‐M; Kwan, Johnny S‐H; Chow, Chit; Tin, Edith K‐Y; Chung, Lau‐Ying; Li, Hui; Wong, Shela S‐Y; Chau, Shuk‐Ling; Chan, Yuk Yu; et al. (The Journal of pathology, 2020)
Serrated polyps are a clinically and molecularly heterogeneous group of lesions that can contribute to the development of colorectal cancers (CRCs). However, the molecular mechanism underlying the development of serrated lesions is still not well understood. Here, we combined multiple approaches to analyze the genetic alterations in 86 colorectal adenomas (including 35 sessile serrated lesions, 15 traditional adenomas, and 36 conventional adenomatous polyps). We also investigated the in vitro and in vivo oncogenic properties of a novel variant of the NCOA4–RET fusion gene. Molecular profiling revealed that sessile serrated lesions and traditional serrated adenomas have distinct clinicopathological and molecular features. Moreover, we identified receptor tyrosine kinase translocations exclusively in sessile serrated lesions (17%), and the observation was validated in a separate cohort of 34 sessile serrated lesions (15%). The kinase fusions as well as the BRAF and KRAS mutations were mutually exclusive to each other. Ectopic expression of a novel variant of the NCOA4–RET fusion gene promoted cell proliferation in vitro and in vivo, and the proliferation was significantly suppressed by RET kinase inhibitors. All of these underscored the importance of mitogen‐activated protein kinase (MAPK) pathway activation in the serrated pathway of colorectal tumorigenesis. In addition, we demonstrated that the kinase fusion may occur early in the precursor lesion and subsequent loss of TP53 may drives the transformation to carcinoma during serrated tumorigenesis. In conclusion, we identified kinase fusions as a significant alternative driver of the serrated pathway in colorectal cancer development, and detecting their presence may serve as a biomarker for the diagnosis of sessile serrated lesions. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.